Examining the impact of the Respect in Sport Parent Program on the psychosocial experiences of minor hockey athletes - Tamminen, K. A.; McEwen, C. E.; Kerr, G.; Donnelly, P. (Journal of Sports Sciences, 2020)
Models of positive youth development suggest that athletes may be influenced by parent education programmes; however, there is little research examining the impact of such programmes on athlete outcomes. This study examined the impact of the Respect in Sport Parent Program on athlete outcomes among minor hockey players over three years. This study consisted of cross-sectional and longitudinal online surveys measuring athletes` positive and negative developmental experiences, prosocial and antisocial behaviours, parental support and pressure, and sport enjoyment and commitment. Athletes completed at least one online survey during the study period (N = 366; 84.2% males; 14-19 years of age; M = 15.4 years), and 83 athletes completed multiple surveys for longitudinal analyses. Cross-sectional results comparing athletes in leagues adopting the programme at different time points indicated significant differences in prosocial behaviours towards teammates. Multilevel longitudinal analyses revealed improvements in athletes` antisocial behaviours towards opponents, initiative, goal setting, and cognitive skills over time, regardless of whether they were in a league that implemented the programme. However, athletes in leagues that implemented the programme during the study reported greater improvements in antisocial behaviours towards opponents, and there were trends with respect to improved personal and social skills. These findings provide suggestions to improve the delivery and impact of parent education programmes in youth sport.